La ventilazione non-invasiva a pressione positiva nell’insufficienza respiratoria acuta ipercapnica: 10 anni di esperienza clinica di una Unità di Terapia Semi-Intensiva Respiratoria (2010)
BackgroundAlthough several prospective controlled randomized trials demonstrated the success of non-invasive positive pressure ventilation (NIV) in selected cases of acute hypercapnic respiratory failure (IRA) in setting with different care levels, clinical practice data about the use of NIV in the “real world” are limited.AimTo report the results of our clinical experience in NIV applied for IRA in the Respiratory Semi-Intensive Care Unit (UTSIR) allocated within the Respiratory Division of Arezzo in the years 1996-2006 in terms of: tolerance, effects upon arterial blood gases, success rate and predictors of failure.MethodsThree hundred filthy of the 1484 patients (23.6%) consecutively admitted for IRA to our Respiratory Division during the study period received NIV in addition to standard therapy, according to the pre-defined routinely used criteria.ResultsEight patients (2.3%) did not tolerated NIV because of mask discomfort, while the remaining 342 (M: 240, F: 102; median (interquartiles) age: 74.0 (68.0-79.3) yrs; COPD: 69.3%) were ventilated for >1 hour. Arterial blood gases significantly improved after two hours of NIV (mean (standard deviation) pH: 7.33 (0.07) versus 7.28 (7.25-7.31), p<0.0001; PaCO2: 71.4 (15.3) mmHg versus 80.8 (16.6) mmHg, p<0.0001; PaO2/FiO2: 205 (61) versus 183 (150-222), p<0.0001). NIV avoided intubation in 285/342 (83.3%) with an hospital mortality of 14.0%. NIV failure was independently predicted by the Apache III (Acute Physiology and Chronic Health Evaluation III) score, the body mass index and by the late failure of NIV (> 48 hrs of ventilation) after an initial positive response.ConclusionsAs results of our ten-year’s clinical experience performed in a UTSIR, NIV is confirmed to be well tolerated, effective in improving arterial blood gases and useful in avoiding intubation in most IRA episodes non-responder to standard therapy.